Sparse Recovery for Bistatic MIMO Radar Imaging in the Presence of Array Gain Uncertainties - Jun Li; Shengqi Zhu; Xixi Chen; Li Lv; Guisheng Liao; Menglei Yi (International Journal of Antennas and Propagation)
A sparse recovery based transmit-receive angle imaging scheme is proposed for bistatic multiple-input multiple-output (MIMO) radar. The redundancy of the transmit and receive angles in the same range cell is exploited to construct the sparse model. The imaging is then performed by compressive sensing method with consideration of both the transmit and receive array gain uncertainties. An additional constraint is imposed on the inverse of the transmit and receive array gain errors matrices to make the optimization problem of the CS solvable. The image of the targets can be reconstructed using small number of snapshots in the case of large array gain uncertainties. Simulation results confirm the effectiveness of the proposed scheme.